Effect of high-flow nasal therapy on patient-centred outcomes in patients at high risk of postoperative pulmonary complications after cardiac surgery: update to the statistical analysis plan for NOTACS, a multicentre adaptive randomised controlled trial - Sarah N. Dawson; Yi-Da Chiu; Andrew A. Klein; Melissa Earwaker; Sofia S. Villar; on behalf of the NOTACS study team (Trials)
Abstract Background The NOTACS trial will assess the efficacy, safety and cost-effectiveness of high-flow nasal therapy (HFNT) compared to standard oxygen therapy (SOT) on the outcomes of patients after cardiac surgery. Methods/design NOTACS is an adaptive, international, multicentre, parallel group, randomised controlled trial, with a pre-planned interim sample size re-estimation (SSR). A minimum of 850 patients will be randomised 1:1 to receive either HFNT or SOT. The primary outcome is days alive and at home in the first 90 days after the planned surgery (DAH90), with a number of secondary analyses and cost-effectiveness analyses also planned. The interim SSR will take place after a minimum of 300 patients have been followed up for 90 days and will allow for the sample size to increase up to a maximum of 1280 patients. Results This manuscript provides detailed descriptions of the design of the NOTACS trial and the analyses to be undertaken at the interim and final analyses. The main purpose of the interim analysis is to assess safety and to perform a sample size re-estimation. The main purpose of the final analysis is to examine the safety, efficacy and cost-effectiveness of HFNT compared to SOT on the outcomes of patients after cardiac surgery. Discussion This manuscript outlines the key features of the NOTACS statistical analysis plan and was submitted to the journal before the final analysis in order to preserve scientific integrity under an adaptive design framework. A previous version of this SAP was published prior to the interim analysis (Dawson, 2022). The NOTACS SAP closely follows published guidelines for the content of SAPs in clinical trials (Gamble, 2017). Trial registration ISRCTN14092678 . (13 May 2020).